Particle-resolved computational fluid dynamics simulation of the heat transfer in fixed-bed reactors for heterogeneous catalysis: A review - Fang, Xu; Fang, Xu; Qi, Beidi; Liu, Jingrong; Markthaler, Simon; Elhaus, Nora; Karl, Jürgen (International Journal of Heat and Mass Transfer, 2025)
For a variety of industrial processes, catalytic fixed-bed reactors are essential and pose problems in respect to the optimization of internal heat distribution. This review assesses the progress made in Particle-Resolved Computational Fluid Dynamics (PRCFD) in analyzing the internal heat transfer in these reactors. Factors affecting heat transfer at the level of the overall bed configuration and at the level of individual particle features are discussed. By comprehensively summarizing the past PRCFD studies on heat transfer analysis in fixed-bed reactors, it provides valuable insights for the further development of PRCFD in this field, to improve the thermal management and guide future optimization of fixed-bed reactors. Moreover, suggestions are provided on simulation pathways that involve combining multiple Computational Fluid Dynamics (CFD) models, such as PRCFD, Particle-Resolved Direct Numerical Simulations (PRDNS), and effective homogeneous CFD, to simulate heat transfer within fixed-bed reactor systems in different scales and scenarios.
CRIS-Team Scopus Importer:2025-06-06
Keywords: Computational Fluid Dynamics Simulation; Fixed-Bed Reactor; Heat Transfer; Particle-Resolved